Leverage : a novel - Gowani, Amran (Atria Books, 2025)
"A hotshot hedge fund employee must risk everything to save his job--and his life--in this timely and darkly funny thriller about race, power, and the corrupting influence of the almighty dollar. Ali "Al" Jafar is a rising star at notorious hedge fund Prism Capital, but fortunes change fast on Wall Street. When his biggest investment goes up in smoke, Al loses $300 million--and his fragile sense of self-worth--in a single afternoon. He's certain he'll be fired, but Prism's obscenely rich and politically connected founder isn't that merciful. Instead, he gives Al an impossible ultimatum: recover the lost money in three months or become the fall guy for the government's insider-trading investigation into the firm. Desperate and depressed, Al turns to high finance's dark side, where he battles back-stabbing coworkers and cutthroat competitors and digs himself into an even deeper hole. As the clock winds down, and the pressure mounts, Al's mental health deteriorates. To survive, he'll have to out fox one of the world's most powerful men and decide if he values the dearest asset of all: himself." --